Vortex behaviour and velocity characteristics of jets issuing from hybrid inclined elliptic nozzles - New, T. H. (2013)
An experimental study on elliptic nozzles with hybrid flat- and inclined-sections is reported here. The hybrid flat and inclined sections are imposed along either the major- or minor-plane of the nozzles (HIN A and B nozzles respectively). For HIN A, results show prevalent pairings between adjacent vortex filaments and induced vortex-loops in the immediate vicinity of the flat-section to produce coalesced vortex roll-ups. Once they detach entirely from the nozzle, they proceed to undergo flow changes resembling that of conventional elliptic jets. HIN B also leads to near-field vortex pairings but produce discrete inclined vortex roll-ups instead, with accompanying delay in rib structure formations. The roles of induced vortex-loops are significantly more limited in the present elliptic HIN than circular HIN investigated previously, due to the dominance of elliptic braid vortices. HIN A produces significantly larger centerline velocity decay, as well as higher turbulence levels in the near vicinity of the nozzle exit. Vectoring of axial jet momentum is more apparent for HIN B, where cross-stream entrainment is also relatively larger. Half-jet width results also demonstrate that both nozzle types eventually produce elliptic jets that undergo axis-switching. Lastly, momentum thickness results suggest that the present nozzle lip-modifications significantly enhance mixing characteristics along the plane upon which they are imposed in both HIN A and B.